In Vitro Assessment of 36 CYP2C9 Allelic Isoforms Found in the Chinese Population on the Metabolism of Glimepiride - Dai, Da‐Peng; Wang, Shuang‐Hu; Geng, Pei‐Wu; Hu, Guo‐Xin; Cai, Jian‐Ping (Basic & clinical pharmacology & toxicology, 2014)
Of the 57 reported CYP2C9 alleles, to date, 36 of them have been identified in the Chinese population. The aim of this study was to assess the catalytic characteristics of these allelic isoforms and their effects on the metabolism of glimepiride in vitro. Baculovirus‐mediated expressing system was used to highly express wild‐type and the 35 CYP2C9 allelic variants in insect cell microsomes. Then, the enzymatic characteristics of each variant were evaluated using glimepiride as the substrate. Reactions were performed at 37°C with the insect microsomes and 0.125–10 μM glimepiride for 40 min. After termination, the products were extracted and used for signal collection by LC‐MS/MS. Of the 36 tested CYP2C9 allelic isoforms, only four variants (CYP2C9.40, CYP2C9.47, CYP2C9.51 and CYP2C9.54) exhibited similar relative clearance values to that of wild‐type CYP2C9.1. In addition, one variant (CYP2C9.36) showed a higher intrinsic clearance value than the wild‐type protein, while the remaining 30 CYP2C9 allelic isoforms exhibited significantly decreased clearance values (from 0.1% to 87.2%) compared to CYP2C9.1. This study provided the most comprehensive data on the enzymatic activities of all reported CYP2C9 variants in the Chinese population with regard to the commonly used antidiabetic drug, glimepiride. Our results indicate that most of the tested rare alleles significantly decrease the catalytic activity of CYP2C9 variants towards glimepiride hydroxylation in vitro.